Impacts of the Pandemic on the Sustainability of Urban Mobility in the Pandemic Period - Martins , Ketryan B.; Brasileiro, Luzenira Alves (ANAP Brazil, 2021)
The aim of this work is to analyze the influence of the pandemic on the mobility of the people interviewed in the city and on the impacts related to the sustaintability of these cities during the pandemic period. It was developed based on data collection by interviewing users of transport systems in different cities in Brazil, which was carried out remotely using a form applied by the Google Forms platform. After tabulating the data, the number of people who used public transport and started to use other modes of locomotion were analyzed, in addition to the travel time for each passenger; and thus, the case study was carried out. Through the results obtained in the research, it was found that the use of automobile, on foot and motorcycle increased, obtaining the value of 9%, 5% and 2%, respectively, more than previously; however, the use of bicycles remained at 5% among the people who answered the form. In addition, it was possible to obtain that 41% of people who traveled for less than 30 minutes by car would possibly be people who could use the bicycle, if there were government incentives, which would make the city more sustainable. The results show that the convergence of data from different cities indicates a consensus among the Brazilian population that there is a need to maintain security in urban mobility systems, as it is a basic service needed by the entire population. KEYWORDS: Urban Mobility. COVID-19. Pollution.